Candida bromeliacearum sp nov and Candida ubatubensis sp nov., two yeast species isolated from the water tanks of Canistropsis seidelii (Bromeliaceae) - Ruivo, CCC; Lachance, M. A.; Rosa, C. A.; Bacci, M.; Pagnocca, F. C. (Soc General Microbiology, 2005)
Strains belonging to two novel yeast species, Candida bromeliacearum and Candida ubatubensis, were isolated from the bromeliad tank of Canistropsis seidelii (Bromeliaceae) in a sandy coastal plain (restinga) ecosystem site in an Atlantic rainforest of south-eastern Brazil. These species were genetically distinct from all other currently accepted ascomycetous yeasts, based on sequence divergence in the D1/D2 domains of the large-subunit rDNA and in the small-subunit rDNA. The species occupy basal positions in the Metschnikowiaceae clacle. The type strains are Candida bromeliacearum UNESP 00-103(T) (=CBS 10002(T) = NRRL Y-27811(T)) and Candida ubatubensis UNESP 01-247R(T) (=CBS 10003(T) = NRRL Y-27812(T)).